A "Three‐in‐One" Multifunctional Probe for Bcl‐2/Mcl‐1 Profiling and Visualizing in Situ. (16th October 2020) - Zhang, Xiaodong; Wang, Ziqian; Guo, Zongwei; Song, Ting; He, Nianzhe; Zhu, Junjie; Cao, Keke; Zhang, Zhichao
Abstract: Bcl‐2 and Mcl‐1, the two arms of the anti‐apoptotic Bcl‐2 family proteins, have been identified as key regulators of apoptosis and effective therapeutic targets of cancer. However, no small‐molecular probe is capable of profiling and visualizing both Bcl‐2 and Mcl‐1 simultaneously in situ . Herein, we report a multifunctional molecular probe (BnN3 ‐OPD‐Alk) by a "three‐in‐one" molecular designing strategy, which integrated the Bcl‐2/Mcl‐1 binding ligand, fluorescent reporter group and photoreactive group azido into the same scaffold. BnN3 ‐OPD‐Alk exhibited sub‐micromolar affinities to Bcl‐2/Mcl‐1 and bright green self‐fluorescence. It was then successfully applied for Bcl‐2/Mcl‐1 labeling, capturing, enriching, and bioimaging both in vitro and in cells. This strategy could facilitate the precise early diagnosis and effective therapy of dual Bcl‐2/Mcl‐1‐related diseases. Abstract : Double vision : A "three‐in‐one" multifunctional probe was designed by integrating the Bcl‐2/Mcl‐1 binding ligand, a fluorescent reporter group and a photoreactive group into the same scaffold, and further applied for protein profiling and bioimaging of both Bcl‐2 and Mcl‐1 simultaneously in situ .